IPT uptake among child contacts of TB patients: Experience from the Indus Hospital TB program, Karachi, Pakistan. (March 2015) - Jafri, Rabab; Malik, Amyn Abdul; Hussain, Hamidah; Hussain, Sadaf; Khatoon, Fatima; Asif, Khujista; Amanullah, Farhana
Abstract: Background: Infants and young children are particularly susceptible to developing tuberculosis (TB) following exposure and infection, and isoniazid preventive therapy can substantially reduce this risk. This evidence-base provides the rationale for the policy and guidelines to screen and manage children that are household contacts of TB cases, prioritizing those with sputum smear-positive TB. The guidelines have been in place for decades, but are rarely implemented. IPT programs in high-TB burden countries are rare and fraught with low uptake and low rates of therapy completion. Methods: This study describes the demographics and outcomes of contact management and the IPT program for <5 years old at the Indus Hospital in Karachi, Pakistan from 2011 to 2014. Children <5 years old in contact with newly diagnosed sputum smear-positive pulmonary TB patients were referred by the counselor for contact evaluation. All children underwent a history, physical, CXR and TST. All contacts were started on IPT based on WHO recommendations after confirming that they had no TB disease. Outcomes were defined as children who were enrolled, started on IPT but never returned for follow-up (primary default), children who had one or more follow-up visits but did not complete treatment (default) and children who completed IPT (treatment completed). Results: A total of 240 children were enrolled in the Indus IPT program from 2011 to 2014. Of these, data from 184 contacts was analyzed in detail as the remainder were still on IPT. All children enrolled were less than 5 years of age (mean age 3 years) and 96 (52%) were males. Of all the enrolled children, 76/240 (31.6%) were <5% weight for their age (underweight), of these 52% were female children. A symptom of either cough or fever was reported by 29/184 (15.7%) children; however, all responded to routine antibiotics and did not have CXR findings suggestive of TB disease. Of the enrolled who had a TST done, 12/209 (5.8%) had a positive result. Analysis of outcomes revealed that only 60/184 (32.6%) completed 6 months of IPT (with no gender predisposition). Among those who completed therapy, none developed TB disease during follow-up. Outcome trends revealed an increase in completion rate (40% in 2013 compared with 26% in 2012), which may reflect improvement in counseling services in 2013. Children who had an initial symptom or were underweight at the start of IPT were more likely to complete treatment ( p < 0.01). Conclusion: Despite a large cohort of TB patients in the Indus TB program-5487 SS+ patients registered during the study period – this IPT program enrollment has been low. A high rate of patient default after the first visit indicates a lack of understanding about the benefit and safety of preventive therapy in young children among families of TB patients, and awareness enhancing efforts by community field teams will help improve outcomes. It is vital that the National TB Program strengthens and expands contact management with a community-based approach and incentives.